Visuals for teaching culture: an analysis of German as a second language textbooks - Karolína Pešková (Pedagogická Orientace, 2012)
The study presents results of a quantitative analysis of visuals for teachingculture in German language textbooks. The research sample consisted of fourtextbooks for teaching German as a second foreign language at lower secondaryschools. The results showed some tendencies which the textbooks have in common,particularly concerning types and contents of the visuals. On the contrary, the maindifferences between the textbooks were identified in functions of the visuals. Basedon the findings of the analysis some tips on improving the textbooks are suggested atthe end of the study.